Integrated approach to facilitate stakeholder participation in the control of endemic diseases of livestock: The case of peste des petits ruminants in Mali - Dione, Michel M.; Traoré, Ibrahima; Kassambara, H.; Sow, A.N.; Touré, C.O.; Sidibé, C.A.K.; Séry, A.; Yena, A.S.; Wieland, Barbara; Dakouo, M.; Diall, O.; Niang, M.; et al. (Frontiers Media, 2019)
In Mali, small ruminants (SRs) are an important means for enhanced livelihood through income generation, especially for women and youth. Unfortunately, opportunities for livestock farmers to tap into these resources for economic growth are hindered by high burden of endemic diseases such as peste des petits ruminants (PPR). A key component for the control of PPR is vaccination of SRs. However, low participation of farmers to vaccination was identified by stakeholders of the livestock value chains as a key constraint to successful vaccination programs. This study was implemented in the framework of a project which aimed at improving the domestic ruminant livestock value chains in Mali by upscaling proven interventions in animal health, feeds and feeding and livestock marketing. The objectives of the study were to review the context of livestock vaccination in Mali and evaluate the impact of innovation platforms (IP) as a means for engaging stakeholders in the vaccination process. Desk review, key informant interviews (KII) and net-mapping were used to understand the context of livestock vaccination, while vaccination coverage and sero-monitoring together with group interviews were used to measure the impact of the intervention. IPs were created in 24 communes in three regions: 15 IPs in Sikasso, 4 IPs in Mopti and 5 IPs in Timbuktu. They developed work plans and implemented activities focusing on improving interaction among key vaccine chain delivery stakeholders such as farmers, private veterinarians, vaccine manufacturers, local leaders and public veterinary services; involving them in the planning, implementation and evaluation of vaccination programs and fostering knowledge sharing, communication and capacity building. After 2 years of implementation of IPs, vaccination coverage for SRs increased significantly in target communes. During the first year, seroprevalence rate for PPR increased from 57% (CI95: 54–60%) at baseline to 70% (CI95: 67–73%) post-vaccination in Sikasso region, while in Mopti region, seroprevalence increased from 51% (CI95: 47–55%) at baseline to 57% (CI85: 53–61%) post-vaccination. Stakeholder engagement in the vaccination process through facilitated IPs was successful in fostering participation of farmers to vaccination. However, a sustainable vaccination strategy for Mali would benefit from consolidating the IP model, supported by Government investment to strengthen and adjust the underlying public-private-partnership.